2019
DOI: 10.1109/jphotov.2019.2899741
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Soiling Rate Determination and Detection of Cleaning Events in Utility-Scale PV Plants

Abstract: As the deployment rate of PV power plants continues to soar, the need for robust, scalable methods for performance analytics increases. In this paper, we demonstrate the usefulness of one approach for quantifying soiling rates in utility-scale PV power plants endogenously, i.e., directly from the production data. The temperature corrected performance ratio, normalized to a clean state, is used to derive the soiling ratio (SR). Cleaning events, caused by either rain or manual cleaning, are automatically detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The dust accumulation effect on PV panels in the MENA region has been assessed in [118], and it has been noted that the cleaning interval can be 12-15 days. Using an endogenous method, the soiling rate in three utility-scale PV systems located in the Middle East has been calculated to be about 0.1% per day [125]. In [38], the optimal cleaning frequency of PV panels in a hot desert climate has been recommended to be weekly, especially during summers.…”
Section: Frequency Of Cleaningmentioning
confidence: 99%
“…The dust accumulation effect on PV panels in the MENA region has been assessed in [118], and it has been noted that the cleaning interval can be 12-15 days. Using an endogenous method, the soiling rate in three utility-scale PV systems located in the Middle East has been calculated to be about 0.1% per day [125]. In [38], the optimal cleaning frequency of PV panels in a hot desert climate has been recommended to be weekly, especially during summers.…”
Section: Frequency Of Cleaningmentioning
confidence: 99%
“…The use of monthly mean soiling rates rather than a fixed soiling rate was proposed to represent better the soiling seasonality in FRP (Micheli et al, 2020a). Skomedal et al (Skomedal et al, 2019) proposed to modify the SRR cleaning detection equation in conditions of high data noise to d (Q 3 + IQR), with d being a site-specific parameter. In addition, they introduced some additional filters to remove outliers.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Skomedal et al. ( Skomedal et al., 2019 ) proposed to modify the SRR cleaning detection equation in conditions of high data noise to (Q 3 + IQR), with being a site-specific parameter. In addition, they introduced some additional filters to remove outliers.…”
Section: Soiling Extraction Algorithmsmentioning
confidence: 99%
“…Cleanings were identified in those dates in which a positive shift in the performance data larger than 3 + 1.5 • occurred. While some authors have suggested site-specific tuning of this equation [13], in this work it has been used in its original version; same for all the sites.…”
Section: Soiling Profile Extractionmentioning
confidence: 99%